State Participation in Energy Security Provision of the People’s Republic of China - Irina F. Rakhimyanova (Vestnik MGIMO-Universiteta, 2015)
The author investigates the role and place of government in the modern energy sector of China. Due to unprecedented scale industrial processes of modernization and urbanization in China, high rates of economic development, the growth of living standards, China's dependence on energy imports every year is growing significantly. And this trend will continue in the coming decades, or even increase. In the foreseeable future, China will feel an acute shortage of energy resources. In this regard, there is a growing concern of the Chinese state-owned energy companies. Obviously, such a prospect is the Chinese leadership worries associated with the risk of failure in international transfers, chronic instability in the region, exporting energy, and the vicissitudes of the global energy. This problem is considered on the analysis of materials of the White books, special attention given to White book «China's energy policy - 2012». The article outlines the contours of energy security of China, the role of major players, including public authorities, government energy corporations, private businesses and the population. Particular attention is given to the Commission of National Development and Reforms, which main function is to form the five years' development plans. The special attention is given to the Concept of National Security of the China. Although attention is paid to issues related to the provision of energy interests of China abroad, including the production and transportation of energy resources, cooperation with governments of countries rich in raw materials. Analyzes the role of the state in providing control over the energy segment, in the framework of China's involvement to globalization process.